The The Utilizing Fruit and Vegetable Peels as a Way to Maintain a Healthy Environment - Aina, Mia; Lisani, Lisani; Farni, Yulfita; Suseno, Rahayu; Susanti, Nova (CV. Media Digital Publikasi Indonesia, 2024)
Fruit and vegetable peels are a common type of organic waste generated in households. Due to their high water content, they decompose naturally. However, if left unattended, these peels undergo anaerobic bacterial decomposition, leading to unpleasant odors and detrimental environmental impacts. Fruit and vegetable peels have the potential to be transformed into valuable resources. One such method is by converting them into eco-enzyme. Eco-enzyme is a complex organic solution produced through the fermentation of fresh fruit and vegetable peels, brown sugar, and water. The resulting liquid is typically dark brown with a characteristically fresh, sour aroma. In RT 24, Simpang Rimbo, Jambi City, many housewives were unaware of the benefits of processing fruit and vegetable peels and lacked understanding of the distinction between organic and inorganic waste. This community service project aimed to reduce organic waste and its associated air pollution by promoting the production of eco-enzyme from fruit and vegetable peels. The project involved several stages: preparation, pretest, socialization, training, and posttest. The results indicated a high level of enthusiasm among participants and a significant improvement in their knowledge of organic waste management after the training